Development of 3dimensional Diorama in The Natural Science Learning Especially Lesson of Ekosistem for Grade V Students - Prabowo, Desi Wulandari, Dady Mukti (Elementary School Teacher, 2018)
Sains education is the one of lesson that must be given for student  of elementary school, but in fact, Sains education still unoptimally done. Based on datas of observation, interview, and document that be found at Kalibanteng Kidul 02 Semarang State Elementary School is showed information that there is problem with the relevance learning media is still low. So, need to be developed 3 dimension diorama media in sains education. The purpose of this research is to describe the steps of developing 3 dimesion diorama media, to know about validity  of  3  dimension  diorama  media,  and  to  know  about  efectivity  of  3  dimension  diorama  media  in  the learning.  Type  rsearch  is  Research  and  Development  (R&D)  with  some  step  are  pra  research,  collecting  data, preparing the media design, product validation, product reparation, small scale test,  big scale test, and the last product.  Research  population  is  all  student  of  grade  V  at  Kalibanteng  Kidul  02  Semarang  State  Elementary School.  Research  sample  is  student  f  grade  V  with  jenuh  sample  technic.  Collecting  datas  technic  are observation,  interview,  test,  angket,  and  documentation.  Analyzing  data  technic  use  analyzing  product  data, analyzing first data/normality test, T test, and N-Gain test. The result of the research shows that 3 dimension diorama media can be used in sains educational learning with the value percentage from media specialist is 94%, content specialist is 97%, media practicy is 97%, and content practicy is 93% with Ttest result is T -assesment (7,396) is bigger than T-table (1,671) and N -Gain test result is 0,7063 with high criteria. This research conclusion is  effectivally  be  used  in  sains  educational  learning  toward  student  learning  result.  Instruction  for  the  next research can use 3 dimension diorama media in other lesson by adapted with component and design is related with the content that be teach.